Evolving preferences and policy advice in democratic society - Viktor J. Vanberg (Max Planck Institute of Economics, 2009)
The theoretical consistency and practical applicability of traditional welfare economics has long been subject to controversy. More recently the challenge has been added from evolutionary approaches that the individual preferences on which the welfare calculus is based are themselves subject to change. The purpose of the present paper is twofold. It takes, firstly, a closer look at the discussion on the need and feasibility of an evolutionary welfare economics that accommodates evolving preferences. The particular focus is on proposal advanced by three authors, Carl Christian von Weizsäcker, Ulrich Witt and Robert Sugden. And it seeks, secondly, to show that the constitutional economics paradigm can deal with the evolving-preferences-issue in a more coherent and consistent way than approaches that remain within the mind-frame of welfare economics.
Keywords: 330